Factors Associated with Adherence to Iron-Folic Acid Supplementation among Adolescent Girls in the Working Area of Kedungwuni 1 Community Health Center - Aghnia Desy puspitasari; Ardiana Priharwati; Wahyuningsih Wahyuningsih; Nur Lu’lu Fitriyani (Jurnal Kesmas Prima Indonesia, 2026)
Iron deficiency anemia is a major global and national health threat among female adolescents, including in Kedungwuni. Despite extensive iron tablet distribution programs, compliance rates remain highly problematic. This study aimed to analyze the determinants of compliance with Iron-Folic Acid (IFA) tablet consumption through the Health Belief Model (HBM) lens. A quantitative cross-sectional design was conducted among eleventh-grade female students within the work area of Puskesmas Kedungwuni 1. A sample of 250 respondents was selected via proportional random sampling. Data were gathered using validated structural questionnaires and analyzed using Chi-Square and Fisher’s Exact tests (? = 0,05). The results showed a statistically significant relationship between perceived susceptibility (p = 0,024)  and perceived barriers (p = 0,018) with IFA tablet consumption compliance. Respondents who felt susceptible to the impacts of anemia had higher motivation to comply, whereas perceived barriers such as nausea, dizziness, and the fishy odor of the tablets became the main obstacles that reduced compliance. Variables of knowledge (p = 0,934), perceived severity (p = 0,921) perceived benefits (p = 0,634) self-efficacy (p = 0,122), and family support (p = 473) were not significantly associated (? > 0,05). Compliance is heavily driven by how vulnerable adolescents feel toward anemia and how they manage sensory barriers such as nausea or foul smell.